Hepatoprotective activity of Eucalyptus camaldulensis extract in murine malaria mediated by suppression of oxidative and inflammatory processes - Aljawdah, Hossam M. A.; Abdel-Gaber, Rewaida; Al-Shaebi, Esam M.; Thagfan, Felwa A.; Al-Quraishy, Saleh; Qasem, Mahmood A. A.; Murshed, Mutee; Mares, Mohammed M.; Al-Otaibi, Tahani; Hawsah, Maysar Abu; Dkhil, Mohamed A. (Frontiers in Cellular and Infection Microbiology, 2022)
Herbal extracts are promising agents against various parasitic diseases, such as malaria. This study aimed to evaluate the ameliorative action of Eucalyptus camaldulensis extract (ECE) against hepatic damage caused by Plasmodium chabaudi infection. Mice were allocated into five groups as follows: two groups served as the control non-infected groups that received distilled water and ECE, respectively; subsequent three groups were infected with 106 P. chabaudi parasitized erythrocytes; the last two groups were infected with the parasite and then treated with ECE and chloroquine. On day 8 post-infection, the parasite count increased inside erythrocytes (59.4% parasitemia in the infected group). Parasitemia was successfully reduced to 9.4% upon ECE treatment. Phytochemical screening using GC mass spectrometry revealed that ECE contained 23 phytochemical components. Total phenolics and flavonoids in ECE were 104 ± 2 and 7.1± 3 µg/mL, respectively, with 57.2 % antioxidant activity. ECE ameliorated changes in liver histopathology and enzymatic activity of alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase. In addition, ECE prevented oxidative damage induced by the parasite in the liver, as evidenced by the change in the liver concentrations of glutathione, nitric oxide, malondialdehyde, and catalase. Moreover, ECE was able to regulate the expression of liver cytokines, interleukins-1β and 6, as well as IFN-γ mRNA. ECE possesses antiplasmodial, antioxidant, and anti-inflammatory activity against liver injury induced by the parasite P. chabaudi.